2020
DOI: 10.14314/polimery.2020.11.5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of halloysite on the physicochemical, mechanical and biological properties of polyurethane-based nanocomposites

Abstract: The impact of the addition of the nanofiller -halloysite -on the mechanical, physicochemical and biological properties of a nanocomposite, in which thermoplastic polyurethane fulfilled the role of the matrix was investigated. The nanocomposite was obtained by extrusion in three variants with 1, 2 and 3 wt % halloysite. The nanostructure of the obtained materials was confirmed using Atomic Force Microscopy (AFM). Based on the mechanical tests carried out, it was proven that the obtained nanocomposites were char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The obtained results showed that the particles of inorganic constituents can significantly reduce the friction coefficient, even small weight fractions of the filler. The influence of filler in the form of inorganic particles on the preservation of the mechanical and physicochemical properties of polymers can be determined by changing the composition of the filler [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results showed that the particles of inorganic constituents can significantly reduce the friction coefficient, even small weight fractions of the filler. The influence of filler in the form of inorganic particles on the preservation of the mechanical and physicochemical properties of polymers can be determined by changing the composition of the filler [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 3D printing of these materials provides many advantages, including unique tailoring to a patient's needs, which is in line with the current trend of personalized medicine [27,28]. The conducted preliminary tests, including plate-tubular halloysite, proved that twin-screw extrusion provides nanocomposites with improved mechanical properties compared with the original matrix with no toxicity to normal cells [29]. The scheme of the research methodology is shown in Figure 1.…”
mentioning
confidence: 71%
“…The cytotoxicity of the tested composites was obtained according to the standard procedures against model cell lines [29,30,32]. The viability and proliferation assays, such as an MTT assay, allowed for biocompatibility of different, natural, or synthetic agents assessments [32,33].…”
Section: Cytotoxicity Test Resultsmentioning
confidence: 99%
“…Cytotoxicity testing of composite samples according to the procedure described earlier [29,30]. Cell viability of normal human dermal fibroblasts (NHDF, Lonza) was assessed using an MTT (3-[4-5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide) test.…”
Section: Cytotoxicity Testing Of Composite Samplesmentioning
confidence: 99%